Urban Agriculture Development : A Strategy to Support Food Security - Juniawati, Juniawati; Hayuningtyas, Maulida (KnE Life Sciences, 2017)
The enhancement of rural-urban migration flows impacts on the enhancement of urban population. It takes more efforts to fulfill the food demand. Now, 80% food stock in urban area is fulfilled from rural area and imports. Urban agriculture development is a strategy to improve food availability, food access and also to support food security. Some of urban agriculture models that have implemented and developed in many country were metropolitan food cluster, rooftop garden, community garden, and vertical farming. This paper is a literature review from various study, research and document relates with urban agriculture. Based on this study, urban agriculture can increase urban community prosperity, environmental sustainability and quality of health. Urban agriculture productivity needs agricultural technology innovation to ensure sustainability of production. Urban agricultural models that is integrated with agricultural technology innovation able to create a resilient urban food systems to accelerate the realization of food security. Keywords: urban agriculture; technological innovaton; food security